Childhood maltreatment amplifies the association between relationship functioning and depressive symptoms among rural African American couples. (April 2022) - King, Victoria; Lavner, Justin A.; Bryant, Chalandra M.; Beach, Steven R. H.
Despite considerable literature documenting associations between relationship functioning and depressive symptoms, there has been relatively little direct examination of this association among African American couples. Likewise, little research has investigated factors that may exacerbate this association. The current study addressed this gap by investigating longitudinal associations between relationship functioning and depressive symptoms among 344 rural African American couples and by examining whether experiences of childhood maltreatment (i.e., childhood physical neglect and childhood physical abuse) amplify this association. Results indicated relationship functioning and depressive symptoms were negatively associated, initially and over time, for both men and women. Additionally, childhood maltreatment moderated several of these associations, such that associations between relationship functioning and depressive symptoms were generally strongest for those reporting greater levels of childhood maltreatment. This pattern of results suggests that experiences of childhood maltreatment may amplify negative associations between adult relationship functioning and depressive symptoms among African American couples, providing further evidence that adverse family-of-origin experiences can contribute to negative consequences later in the life course.